Social Exclusion and Optimal Redistribution - Thomas Aronsson; Spencer Bastani; Khayyam Tayibov (Center for Economic Studies and ifo Institute (CESifo), 2021)
We integrate social exclusion, operationalized in terms of long-term unemployment, into the theory of optimal redistributive taxation. Our results show how an optimal mix of education policy, public employment, and support to the unemployed, in conjunction with optimal income taxation, contributes to redistribution and reduced long-term unemployment. The second-best optimum most likely implies overprovision of education relative to a policy rule that balances the direct marginal benefit and marginal cost, whereas public employment and unemployment benefits are underprovided. Our calibration shows how the policy mix varies with the government's preferences for redistribution and the characteristics of those risking long-term unemployment.
Keywords: H21; J24; J45; I21; 330; long-term unemployment; education; optimal income taxation; public sector employment